SOCIALIZATION AND TECHNICAL TRAINING ON USING E-MAIL FOR STUDENTS TO IMPROVE DIGITAL LITERACY SKILLS - Hallaby, Syarifah Fadiya; Hamama, Syarifah Farissi; Qalbiya, Nurul (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2024)
Students of Biology Education Study Program, Abulyatama University generally come from rural areas and small islands in Aceh. In those areas access to the internet network is still limited. Hence, the development of information and communication technology is also affected. Therefore, many students are not familiar in using the internet and information and communication technology for learning purposes, even the simplest thing in the 4.0 era, such as an e-mail is new for them. Through this community service activity, students are expected to understand how to use e-mail to support the learning process and improve their digital literacy. The activity was carried out in two steps which were (1) socialization and (2) technical training. It was participated by 36 new students in School of Biology Education, Abulyatama University. This activity was successfully conducted. Each student now has their own e-mail that would be used in the learning process and other formal administrative needs. Keywords: socialization, technical training , e-mail, digital literation